British society 1870-1970 - Salt, John (Abersham ; Hulton Educational Publications, 1975)
"Aspects of British Political History, 1815-1914 examines all the major themes, personalities and issues of this important period in a clear and digestible form; introduces fresh angles to long-studied topics; consolidates a great body of recent research; analyses views of different historians; gives concise treatment to complex issues; [is] directly relevant to A-Level and undergraduate questions and courses; [is] carefully organised to reflect the way teachers tackle this course; [is] written by an experienced and renowned textbook author; and [is] illustrated with helpful maps, charts, photographs and cartoons."--BOOK JACKET.
22. Britain and Ireland 1800-1921 -- 23. Primary sources for British political history 1815-1914.
Includes bibliographical references (p. 335-359) and index.
Keywords: Great Britain -- Politics and government -- 19th century; Great Britain -- Politics and government -- 1901-1910.